An efficient multiple access interference suppression scheme in asynchronous femtocells. Issue 14 (1st September 2013) - Banitalebi, Behrouz; Abouei, Jamshid
Abstract : This work considers a code division multiple access (CDMA)‐based femtocell system where a fixed set of subscribed users communicate simultaneously to a femtocell access point (FAP) in an asynchronous fashion during the uplink. The main goal of this paper is to present an augmentation protocol for the physical layer of the CDMA2000 femtocell standard with focus on the multiple access interference (MAI) suppression. The above‐closed access femtocell uses a unique set of cyclic orthogonal binary codes to eliminate the MAI caused by packet collisions. This property ensures that the time and data rate asynchronicity of active nodes in a femtocell produces a zero MAI situation at the FAP. The work investigates the optimality and the effectiveness of such codes in femtocells from the link bit error rate performance in a practical Rayleigh‐fading environment, where Kalman filtering is used at the FAP for the channel estimation. Theoretical findings are verified by simulation evaluations and it is shown numerically a significant improvement in the performance of the proposed scheme when compared with conventional non‐cyclic orthogonal codes in a Rayleigh‐fading channel in the asynchronous femtocell.